cfDNA Key genomic markers in HCV-Induced hepatocellular carcinoma in Egyptian patients - Mohamed Khalifa; Ahmed A. Hmed; Khaled S. Elfeky; Sayed Bakry; Manal El Hamshary; Ahmed R. Sofy (Journal of Genetic Engineering and Biotechnology)
Background: Malignant liver disease is among the highest in the world, with hepatocellular carcinoma (HCC) accounting for up to 90 % of all cases. In Egypt, HCC poses a significant public-health concern, representing 47.17 % of cancer cases. The high incidence of hepatitis C virus (HCV) in the Egypt was a major predisposing factor for HCC. Material: This study included 63 Egyptian HCC patients, 55 % of whom had a history of HCV infection. Methods: Using a paired sampling strategy, approximately 2800 COSMIC mutations from 50 oncogenes and tumor-suppressor genes were NGS sequenced. Results: Total of 381 somatic mutations were identified, 91 mutations detected in the HCC group and 291 in the HCV-related HCC group. The top 10 mutated genes in the non-HCV group were TP53, ATM, EGFR, CDH1, FGFR1, MET, SMAD4, ERBB2, FLT3, and FBXW7, while in the HCV-related HCC group, genes were KIT, ATM, TP53, APC, FBXW7, KDR, RB1, SMAD4, EGFR, and PIK3CA. Conclusion: The present study represents the first comprehensive somatic mutation profile in HCC Egyptian patients. This finding suggests that HCV viral infection played a direct and indirect role in increasing the somatic mutation burden in HCV-related HCC patients and opens new promises of targeted therapies for those patients.